THE ROLE OF THE VILLAGE GOVERNMENT IN EMPOWERING THE COMMUNITY TOWARDS WASTE MANAGEMENT IN GAMPONG JAWA - BANDA ACEH CITY - Dahlawi, Dahlawi; Putri, Salsabila Helga; Fitri, Della Ariska; Lestari, Tria Nadila; Rahmat AR, Juni (JURNAL AL-IJTIMAIYYAH, 2024)
The Gampong government has an important role in empowering the community. This is the case with the Gampong Jawa government, which empowers community groups to manage waste. This research aims to discover the role played by the village government in empowering the community towards waste management in Gampong Jawa, Banda Aceh City. In this study, researchers used qualitative research methods with a descriptive approach. The data sources obtained are primary data from direct interviews with 5 informants in Gampong Jawa Banda Aceh City and secondary data collected from the field and library supporting documents. The data collection techniques used in this research are observation, interviews, and documentation sent directly to the research location. From the results of the study, it can be concluded that the role of the village government in waste management is very necessary for community empowerment of the surrounding environment. Then, the results of the discussion state that the village government's lack of participation and supervision in waste management by the community is a problem. The village government pays little attention to waste management groups in Gampong Jawa. The form of attention of the Gampong government only facilitates transportation facilities, such as garbage trucks and rickshaws, in waste management by the community.